Innovative behavior and leadership: A systematic literature review and future research direction - Muadzah, Syarifah; Herachwati, Nuri (MBR (Management and Business Review), 2024)
This study explores the relationship between innovative work behavior and leadership within organizations through a systematic literature review. Using a systematic review approach, this study analyzes 66 relevant articles from the Scopus database. The findings reveal that leadership styles such as transformational, spiritual, and authentic leadership positively impact innovative behavior. Additionally, mediating and moderating factors, such as job satisfaction and psychological capital, significantly contribute to the leadership-innovation link. However, the literature review is limited by its reliance on the Scopus database, which may exclude relevant studies from other databases or non-indexed sources, potentially introducing selection bias. Despite this, the research lays a solid foundation for future studies and provides practical insights for leaders aiming to promote innovation within their organizations.